If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying x^{2}+ 2x + 195 = 0 Reorder the terms: 195 + 2x + x^{2}= 0 Solving 195 + 2x + x^{2}= 0 Solving for variable 'x'. Begin completing the square. Move the constant term to the right: Add '-195' to each side of the equation. 195 + 2x + -195 + x^{2}= 0 + -195 Reorder the terms: 195 + -195 + 2x + x^{2}= 0 + -195 Combine like terms: 195 + -195 = 0 0 + 2x + x^{2}= 0 + -195 2x + x^{2}= 0 + -195 Combine like terms: 0 + -195 = -195 2x + x^{2}= -195 The x term is 2x. Take half its coefficient (1). Square it (1) and add it to both sides. Add '1' to each side of the equation. 2x + 1 + x^{2}= -195 + 1 Reorder the terms: 1 + 2x + x^{2}= -195 + 1 Combine like terms: -195 + 1 = -194 1 + 2x + x^{2}= -194 Factor a perfect square on the left side: (x + 1)(x + 1) = -194 Can't calculate square root of the right side. The solution to this equation could not be determined.

| 9+12x-3=9x+46-7x | | -3=-2+5 | | 7b-3=-26+24 | | -3=x-2 | | 10=6a+4-9a+a | | 06(x+20)+.8(x-10)=46 | | -6(3-3x-7y)+2y-x= | | -9n+16=-8n-16 | | 2(6x-3)-1=9(3x+2)-10x | | -(m+9n-12)= | | (4K+7)(3K)= | | 7n+12=2.5n-2 | | 6h+5+h=-30 | | 5(x-2)=-3(7-4x) | | p^2+12p+6=0 | | 4(r+8)-5(2r-1)= | | b^2=9 | | y-11.6=-21 | | 9(5+t)-7(t+3)= | | 2x-4x+34=23x-11x+22 | | 4(r-90)+4r=3000 | | 8t-4+3t=0 | | .6=1.5x | | x(6x-1)=12 | | 6(4t-3)+6(4-3t)= | | a+b=-7 | | 690t=3450 | | 10(-6x-6)+8= | | -2(x-3)=1x+5-3x | | -4b+10b(8b+5)= | | 2.3+0.04x=0.1x-0.1 | | 310+380t=3450 | | n-8+6n+6= | | -5x-8x+8=-2x | | -4(1a+1)-3a=-7(2a-3) | | -4v+4v= | | 6x^2-13x-8=0 | | 12x^2-10=7x | | n-9+1+10n= | | 6x+3(4-x)=16 | | -x+4x= | | x=9+-3y | | 8x-15-6x=85-3x | | 6+3x+2= | | 3x-22+4x=10-2x | | 5x+2(x-5)=19 | | 8x-1=7x-14-2x | | 2.4-0.03x=0.44-0.1x | | 6x+2-10= | | 3y+x=9 | | 5x+12(3x+44000)=6473000 | | 4p-10+10p+8= | | 5x^2-17=0 | | 5x^2=55 | | 5x+12(3x+44000)=64730 | | 2x-7=4(x-3)+3x | | 6r-21=-7+8r | | 18(9+4d)=100 | | 4x^2+7=29 | | 6x-12-x=3x+53+x | | 4n+n= | | 5t+2(t-5)=19 | | 7z-4=-8+5z | | -8x-20+6x=6 | | 6x-12-x=3x+53x |

- Equations solver - equations involving one unknown
- Quadratic equations solver
- Percentage Calculator - Step by step
- Derivative calculator - step by step
- Factorization
- Greatest Common Factor
- Least Common Multiple
- System of equations - step by step solver
- Fractions calculator - step by step
- Theory in mathematics